Pengaruh Produk dan Iklan Terhadap Keputusan Pembelian Yamaha Jupiter MX - River Diego Mardjiono (Ecobuss, 2021)
The purpose of this study was to determine the simultaneous and partial influence of products and advertisements and the most dominant variables on the purchase decision of Yamaha Jupiter MX motorcycles. The type of research used is explanatory research. The population is JMC Community (Jupiter MX Club) Surabaya as many as 56 people who know the Jupiter MX ad version of 'Bridge Collapse'. Saturated sampling technique is the entire population. The analysis technique used is multiple regressions with significant tests of F and t. The results of the analysis showed that products and advertisements simultaneously had a significant effect on purchasing decisions. While the results of the analysis partially, it was concluded that: (1) The product has a significant effect on purchasing decisions. (2) Advertising has a significant effect on purchasing decisions. Product variables have a dominant effect on purchasing decisions. Based on the findings of this study, Yamaha manufacturers should still pay attention to product variables and advertising because it is proven to have a large influence on consumer purchasing decisions. As per the lowest score, then the quality of Jupiter MX products needs to be improved. Keyword: Product, Advertisement, Buying Decision.